Classificação automática de modulações mono e multiportadoras utilizando método de extração de características e classificadores SVM - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
Cognitive radio is a new technology that aims to solve the spectrumunderutilization problem, through spectrum sensing, whose objective is to detect the so called spectrum holes. Automatic modulation classi cation plays an important role in this scenario, since it provides information about primary users, with the goal of aiding in spectrum sensing tasks. In the present dissertation, we propose a methodology for multiclass and hierarchical classi cation of modulated signal using support vector machines (SVM), with a set of prede ned parameters. In literature, other works deal with automatic modulation classi cation with SVM and other classi ers, however, few of them take a deep look at classi er design. SVM is known by its high discrimantion capacity, but its performance is very sensitive to the parameters used during classi ers design. With the use of a prede ned set of parameters, we seek to analyze the behavior of the classi er broadly and to investigate the in uence of parameter changes on the constitution of classi ers. In addition, we use one-versus-all and one-versus-one, error-correcting output codes and hierarchical decomposition. Finally, nine types of modulations (AM, FM, BPSK, QPSK, 16QAM, 64QAM, GMSK, OFDM and WCDMA) are used. The types of modulation as well as the decomposition techniques used cover almost all decomposition techniques and modulation classes present in the literature.
Keywords: Cognitive Radio; Automatic Modulatoin Classification; Kfold Cross Validation; Parameter Selection; Error-correcting output codes; Rádio Cognitivo; Modulação Analógicas; Classificação Automática de Modulação; ENGENHARIAS: ENGENHARIA ELÉTRICA